2019
DOI: 10.21873/invivo.11585
|View full text |Cite
|
Sign up to set email alerts
|

Association of Caspase-8 Genotypes With Oral Cancer Risk in Taiwan

Abstract: Background/Aim: Recently, mounting evidence has shown that caspase-8 (CASP8) rs3834129 (-652, 6N insertion/deletion) polymorphism may serve as a genetic biomarker for personal risk of various cancer types. The contribution of CASP8 rs3834129 polymorphism has been investigated in several oral cancer populations, but not in Taiwan. This study investigated the role of CASP8 rs3834129 polymorphism on oral risk in Taiwan. Materials and Methods: CASP8 rs3834129 polymorphic genotypes were determined and their associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…From the viewpoint of oral cancer genomics, there are several biomarkers in the fields of DNA repair activity (27,28), extracellular matrix regulation (17,18), antioxidant capacity (28,29), cell viability (19). All these, in addition to the immune-responsiveness studied here, are contributors to differential susceptibility of individual patients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…From the viewpoint of oral cancer genomics, there are several biomarkers in the fields of DNA repair activity (27,28), extracellular matrix regulation (17,18), antioxidant capacity (28,29), cell viability (19). All these, in addition to the immune-responsiveness studied here, are contributors to differential susceptibility of individual patients.…”
Section: Discussionmentioning
confidence: 98%
“…Investigated controls and cases. Briefly, 958 oral cancer cases were recruited at the China Medical University Hospital in central Taiwan (17)(18)(19). The demographic indexes of the oral cancer patients, including their histological details, were all graded and defined by expert surgeons.…”
Section: Methodsmentioning
confidence: 99%
“…Several polymorphic sites were identified in the CASP8 gene, among which a six-nucleotide insertion/deletion variant was found to have a direct effect on the regulation of CASP8 mRNA. In view of this fact, numerous studies have reported the association of polymorphism with various types of cancer including cancers of neuroblastoma, digestive tract, lung, prostate, breast and bladder [19]. Although this polymorphism produces controversial results in different population groups, it is worthwhile to study the effect of these variants or genetic markers in the South Asian population to derive an association between the same with HNSCC.…”
Section: Resultsmentioning
confidence: 99%
“…Recruited Taiwanese oral cancer cases and controls. In brief, 958 oral cancer patients had been recruited at the China Medical University Hospital (22)(23)(24). The frequencies of their demographic characteristics including age, gender, personal behaviors and tumor sites were summarized in Table I.…”
Section: Methodsmentioning
confidence: 99%